2016
DOI: 10.1590/1807-7692bar2016160007
|View full text |Cite
|
Sign up to set email alerts
|

Do the Board of Directors Composition and the Board Interlocking Influence on Performance?

Abstract: This study analyzes the influence of composition of the Board of Directors and their social relations (board interlocking) on performance of Brazilian companies. A descriptive study based on documentary research was conducted with a total of 1,163 companies' observations and 18,119 standardized observations regarding directors. Simultaneous equations were applied to the data analysis. The survey results showed that, regarding the influence of composition of the Board of Directors on the performance of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
18

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 65 publications
2
10
0
18
Order By: Relevance
“…As a rule, even though previous studies supported the prevailing theories, they similarly display contradictory proof concerning the relationship between a portion of the board of directors' characteristics and the firm value. Open Access Library Journal In recent years, the studies on corporate governance have focused their attention on the analysis of the structure of the board [3] [7] [8] [9] [10] [11]. Yet, the empirical proof on the relationships among board structure and firm value is still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…As a rule, even though previous studies supported the prevailing theories, they similarly display contradictory proof concerning the relationship between a portion of the board of directors' characteristics and the firm value. Open Access Library Journal In recent years, the studies on corporate governance have focused their attention on the analysis of the structure of the board [3] [7] [8] [9] [10] [11]. Yet, the empirical proof on the relationships among board structure and firm value is still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…This key finding is consistent with the King IV report recommended practice (P7RP18) as well as Mans-Kemp et al (2016) where it was recommended that directors should limit their board memberships to give sufficient attention to the activities of all firms which they serve. A case study by Vesco and Beuren (2016) found that the characteristics of the governing board and the practice of board interlocking in Eskom proved to be insignificant with the market value. On the contrary, Habib (2016) found a positive correlation with ROA.…”
Section: H2: Board Interlocks Are Negatively Correlated With Profitabmentioning
confidence: 99%
“…O conselho de administração é um órgão que visa assumir a responsabilidade de tomar decisões em nome dos proprietários de uma organização (ANDRADE et al, 2009). Essa responsabilidade faz o conselho de administração se apresentar como um importante mecanismo para as funções de gestão e controle das organizações BEUREN, 2016). Dessa forma, o conselho se torna um instrumento de criação de valor para a companhia.…”
Section: Introductionunclassified
“…O conselho de administração atua nas organizações como um intermediador entre os acionistas e os administradores, de modo a exercer relevante papel na redução dos conflitos de agência BEUREN, 2016). Tal papel leva diversos autores a destacarem a necessidade de independência do conselho de administração, ou seja, a sua formação por membros externos à companhia, que não sejam acionistas ou componham o quadro de executivos da mesma (VALADARES; LEAL, 2000; ROSSONI; MACHADO-DA-SILVA, 2010; MOURA; BEUREN, 2011;TERJESEN;FRANCISCO, 2015).…”
Section: Introductionunclassified
See 1 more Smart Citation